Situation Report: Czechoslovakia, 7 September 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Charter 77 on the Anniversary of the Soviet Invasion Marshal Ustinov Attends Slovak National Uprising Celebrations The Anniversary: A Closed Book for Open Praise US Ambassador's Letter Published in Rude Pravo Zagladin in Prague Admits Setbacks and Reads Marxist Strictures Warsaw Pact Military Exercises in Czechoslovakia Czechoslovak Catholics Concerned about Growing Ties with Moscow Patriarchate The Pope, the Patriarch, and the Primate of Prague Religious Renaissance in Literature